Comparison of media and growth conditions for culturing enterohepatic Helicobacter species. (1st September 2019) - Ochoa, S.; Martínez, O.A.; Fernández, H.; Collado, L.
Abstract: This research aims to compare the culturing conditions for enterohepatic Helicobacter, evaluating culture media, incubation atmosphere and susceptibility to antimicrobials used to generate selective conditions. Four common media for the closely related genus Campylobacter (Columbia, Bolton, Brucella and CCDA agar), as well as the need for hydrogen in the microaerobic incubation atmosphere, were evaluated. Serial dilutions of 13 strains belonging to six species ( H. apodemus, H. bilis, H. canicola, H. canis, H. equorum and Helicobacter sp.) were inoculated in each media and incubated at 37°C for 48 to 96 h using CampyGen (OXOID) and gaseous exchange (including hydrogen) in parallel. Columbia or Brucella agars were the most appropriate for culturing EHH ( P < 0·05). However, there was no significant difference between the atmospheres evaluated ( P = 0·13). In addition, minimal inhibitory concentration for six antibiotics showed that all isolates were resistant to trimethoprim, whereas for the rest of the antibiotics (cephalothin, cefoperazone, cefsulodin, teicoplanin and vancomycin) the inhibition range was between 8 and 64 μ g ml − 1 . Our findings suggest that Columbia or Brucella media, regardless of the use of hydrogen, can be used for the EHH isolation. In addition, the concentration of antibiotics included in commercial campylobacteria supplements is suitable for EHH species recovery. Significance and Impact of the Study: Enterohepatic Helicobacter (EHH) infections have been associated with several diseases in humans such as acute gastroenteritis, inflammatory bowel disease and hepatobiliary diseases. Although they are frequently detected in clinical samples by molecular methods, only occasionally they are isolated using culture conditions described for the taxonomic related pathogen Campylobacter sp. This is because the optimal conditions for the isolation of EHH have not yet been described, which results in an underestimation of the prevalence and clinical importance of these emerging pathogens. Therefore, this study provides insight for culturing EHH species.